2022
DOI: 10.3390/ijms23031247
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights of Chelator Complexes with Essential Transition Metals: Antioxidant/Pro-Oxidant Activity and Applications in Medicine

Abstract: The antioxidant/pro-oxidant activity of drugs and dietary molecules and their role in the maintenance of redox homeostasis, as well as the implications in health and different diseases, have not yet been fully evaluated. In particular, the redox activity and other interactions of drugs with essential redox metal ions, such as iron and copper, need further investigation. These metal ions are ubiquitous in human nutrition but also widely found in dietary supplements and appear to exert major effects on redox hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 222 publications
(365 reference statements)
0
30
0
Order By: Relevance
“…The extent of the participation of either caeruloplasmin or transferrin in the ferroxidase activity under physiological conditions has not yet been fully investigated. In the meantime, similar properties have been shown by the iron chelating drugs deferiprone, deferasirox and deferoxamine, which can rapidly oxidize ferrous to ferric iron at physiological conditions before the formation of the corresponding ferric iron complexes [15,[35][36][37]. The ferroxidase and iron complex formation activity of the iron chelating drugs is the cornerstone of their antioxidant activity in the Fenton reaction and has been utilized and shown to be related to the powerful antioxidant effects exerted in many in vitro, in vivo and clinical models of oxidative stress [38].…”
mentioning
confidence: 54%
“…The extent of the participation of either caeruloplasmin or transferrin in the ferroxidase activity under physiological conditions has not yet been fully investigated. In the meantime, similar properties have been shown by the iron chelating drugs deferiprone, deferasirox and deferoxamine, which can rapidly oxidize ferrous to ferric iron at physiological conditions before the formation of the corresponding ferric iron complexes [15,[35][36][37]. The ferroxidase and iron complex formation activity of the iron chelating drugs is the cornerstone of their antioxidant activity in the Fenton reaction and has been utilized and shown to be related to the powerful antioxidant effects exerted in many in vitro, in vivo and clinical models of oxidative stress [38].…”
mentioning
confidence: 54%
“…When the Cu(II) ion is reduced by O 2 ●− , this cycle constitutes a Haber–Weiss reaction [ 41 ]. Various metal chelators have differential effects on the generation of HO ● by promoting or inhibiting the Fenton-type reaction depending on the reaction conditions [ 25 ]. In the present study, various amino acids showed different copper-chelating activities, and their effects on the viability of Cu(II) ion-overloaded cells were partly associated with copper-chelating activities.…”
Section: Discussionmentioning
confidence: 99%
“…Chelators can act as either antioxidants or prooxidants by inhibiting or enhancing the transition metal-catalyzed production of ROS [ 25 ]. Thus, it is hypothesized that only certain types of copper chelators may have beneficial effects in cells exposed to high levels of copper ions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to organ toxicity observed in TM patients as a result of excess iron deposition, pathological effects are also suspected from non-transferrin bound iron, which is able to catalyse the formation of free radicals leading to oxidative stress toxicity and progressively to biochemical, subcellular, cellular and tissue damage [63][64][65][66][67][68]. All three chelating drugs and in particular L1 appear to inhibit effectively the iron catalysed free radical damage [69][70][71][72][73].…”
Section: Organs Susceptible To Iron Overload Toxicity Caused By Chron...mentioning
confidence: 99%